Culture and contagion: Individualism and compliance with COVID-19 policy - Chen, Chinchih; Frey, Carl Benedikt; Presidente, Giorgio (Journal of economic behavior & organization, 2021)
•There is significant variation in people’s compliance with lockdown measures introduced by governments to curb the spread of the COVID-19.•Much of the variation can be explained by different cultural traits.•Individualism, which emphasises personal freedom, makes government intervention harder, whereas collectivism, which emphasises the wellbeing of the group, makes collective action easier.•We conclude that cultural factors play a critical role in successful policy implementation. In the first wave of the pandemic, places where geographic mobility declined more rapidly saw fewer cases of COVID-19. And yet, there is significant variation in people’s compliance with the lockdown measures introduced by governments in order to curb the spread of the virus. In this paper, we show that much of this variation can be explained by different cultural traits. Specifically, we advance the hypothesis that individualism, which puts greater value on personal freedom, makes government intervention harder, whereas collectivism, which emphasises the wellbeing of the group, makes collective action easier. We find support for these ideas across 111 countries, but also when exploiting within country variation in the two largest economies in the world: China and the United States. Across a host of specifications, people were less abiding by the lockdown rules in places with greater prevalence of individualistic cultural traits. We conclude that cultural factors play a critical role in successful policy implementation.